DEVELOPING ENGLISH TEACHING MATERIALS USING A DEBATE TECHNIQUE TO IMPROVE THE SPEAKING SKILLS OF THE 8th GRADE STUDENTS AT PERMATA BANGSA SCHOOL - Febyola, Wira Milenia; Ariatna, Ariatna (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2023)
The use of textbooks as a teaching media is similar to the conventional approach to class, applying a repeating strategy that students sometimes see as lacking in enthusiasm. As a result, the students' ability in speaking doesn't grow as expected. The research conducted at Permata Bangsa School Binjai with 19 eighth-grade students as the subjects. This study used a debate technique to cultivate speaking material particular focused on the British Parliamentary Style. This study was categorized as a Research and Development (R&D) with questionnaire, interview as the data. The experts gave 98% for the developed speaking materials which means the suitability of the materials for usage by eighth-grade students at Permata Bangsa School Binjai has been confirmed valid through expert validation. The final product named “Speaking Materials Utilizing a Debate Technique for Eighth Grade Students in Junior High School."